Professional Training of the Future Economics Teachers on the Basis of Group Interaction - Oksana Sarkisova (Pedagogical Discourse, 2015)
In the article the necessity of group interaction in professional training of the future economics teachers is substantiated and the state of the professional training of the future economics teachers in a non-pedagogical university of economics is analysed. The importance of the formation and development of social qualities both of the future economics teachers and of the future specialists in the area of economics is demonstrated. The features of the professional training of the future economics teachers in a non-pedagogical institution of higher education are highlighted. The features of the professional training of the future economics teachers in the classical pedagogical universities are considered. The attention is concentrated on the necessity of training of the future teacher for the organization of interaction of different levels. It is recommended to organize group interaction between the participants of the educational process to raise the effectiveness of the professional training of the future economics teachers.